Approaches for Scaling up the Production of Cell-Cultured Fat Tissue - Yuen Jr, John. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: Joe Tien, Yu-shan Lin, and Qiaobing Xu.; Keywords: Bioengineering, Cellular biology, and Materials Science.